Management Systems for Biannual Seed Crop of Italian Ryegrass (Lolium multiflorum Lam.) Grown at Various Nitrogen Fertilization: I. First-Production Year Characterized by Limited Crop Lodging and High Seed Shattering before Direct Combine-Harvesting - Zlatko Sveˇcnjak, Dario Jareš, Ana Milanovi´c-Litre, Zvonko Pacanoski , Darko Uher and Dubravka Dujmovi´c Purgar (MDPI, Basel, Switzerland, 2022)
Little is known about the best management systems for seed production of Italian ryegrass. The main objective of this study was to determine the influence of management systems on the firstyear seed crop grown under various nitrogen fertilization (0, 60, 120 and 180 kg ha􀀀1). Management systems of single-purpose crops were with (SeedPGR-crop) and without (Seed-crop) plant growth regulator application. The dual-purpose crops incorporated early spring forage cut during stem elongation (EF-seed-crop) and late cut at the onset of heading (LF-seed-crop) followed by seed harvest. Compared to the single-purpose crops, the dual purpose-crops shattered much less seeds but still yielded less because their plants had lower number of visible nodes on stems, shorter ears, fewer spikelets per ear, fewer flowers per spikelet in various ear sections and lighter seeds. Despite similar lodging incidence, the SeedPGR-crop produced relatively small, but significantly larger seed yield than the Seed-crop because plants in the SeedPGR-crop had shorter stems with fewer vegetative tillers, and shattered seeds slightly less. Nitrogen fertilization consistently improved seed yields in all management systems regardless of associated increases in lodging and seed shedding. These yield increments were mainly associated with the increased number of early- and late-formed reproductive tillers, and partly due to improved number of florets per spikelet and slightly heavier seed in early formed reproductive ears. In spite of larger seed losses through shattering, the single-purpose crops largely out-yielded and had higher seed germination than the dual-purpose crops at all nitrogen fertilization rates, with maximized yields produced in the SeedPGR-crop.
Keywords: crop management; ryegrass; plant growth regulator; germination; yield components; seed production